Data Warehouse and Data Mining : Concepts, techniques and real life applications - Kumar, Jugnesh (BPB Online, 2024)
Data warehouse and data mining are essential technologies in the field of data analysis and business intelligence. Data warehouse provides a centralized repository of structured data and facilitates data storage and retrieval. Data mining, on the other hand, utilizes various algorithms and techniques to extract valuable patterns, trends, and insights from large datasets